2017
DOI: 10.3390/en10050682
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Variable Diffuser Vanes on Performance of a Centrifugal Compressor with Pressure Ratio of 8.0

Abstract: Abstract:In numerous applications, centrifugal compressors are required to provide a high pressure ratio with good efficiency while also working in a wide operating range. This is a challenge because as pressure ratio increases, efficiency and operating range inevitably decline. This paper studies the effects of a variable geometry diffuser on the performance and operating range of a centrifugal compressor with high pressure ratios of up to 8.0. The numerical method employed three-dimensional Reynolds-averaged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The plate's position changes in response to a signal from the controller or the thermostat in the area it serves [55]. A VA diffuser's nominal airflow is about 150 cfm at 0.05 pressure drop, or twice the flow rate of a swirl diffuser [56].…”
Section: Ufad System Componentsmentioning
confidence: 99%
“…The plate's position changes in response to a signal from the controller or the thermostat in the area it serves [55]. A VA diffuser's nominal airflow is about 150 cfm at 0.05 pressure drop, or twice the flow rate of a swirl diffuser [56].…”
Section: Ufad System Componentsmentioning
confidence: 99%
“…They showed that a reduction in the leading edge angle results in a shift of the compressor operating range towards lower mass flow rates. By implementing an actuation mechanism, which allows the flexible pivoting of the diffuser vanes, the operating range of the compressor can be adjusted depending on the operating conditions [13,14]. However, gaps between end walls and diffuser vanes, which are necessary for a flexible pivoting concept, cause aerodynamic losses and thus reduce efficiency.…”
Section: Introductionmentioning
confidence: 99%